Kaposi Sarcoma Mimicking Acute Flare of Ulcerative Colitis - Kumar, Vivek (J Investig Med High Impact Case Rep, 2017)
Besides an AIDS-defining illness, Kaposi sarcoma (KS) is also seen in individuals on long-term immunosuppressant therapy. We report KS in a 70-year-old immunocompetent man, which initially mimicked acute flare of ulcerative colitis (UC). He was hospitalized multiple times for complaints of watery diarrhea and tenesmus. Despite treatment with mesalamine, short courses of methylprednisolone, and one dose of infliximab, his symptoms improved only partially. He underwent colonoscopy, which revealed mild active colitis and a mass in the ascending colon. After treatment of acute flare with methylprednisone and mesalamine, he underwent total colectomy with end ileostomy. The histopathology confirmed stage I adenocarcinoma of colon. He continued to experience watery diarrhea, which was attributed to intractable UC, and he underwent protectomy several weeks later. The histopathology of rectum revealed KS. After surgery, watery diarrhea resolved completely. Review of literature suggests KS has been rarely reported in immunocompetent individuals with inflammatory bowel disease.